Spike-specific humoral and cellular immune responses after COVID-19 mRNA vaccination in patients with cirrhosis: A prospective single center study. Issue 2 (February 2023) - Iavarone, Massimo; Tosetti, Giulia; Facchetti, Floriana; Topa, Matilde; Er, Joey Ming; Hang, Shou Kit; Licari, Debora; Lombardi, Andrea; D'Ambrosio, Roberta; Degasperi, Elisabetta; Loglio, Alessandro; Oggioni, Chiara; et al.
Abstract: Background and Aims: COVID-19 mRNA vaccines were approved to prevent severe forms of the disease, but their immunogenicity and safety in cirrhosis is poorly known. Method: In this prospective single-center study enrolling patients with cirrhosis undergoing COVID-19 vaccination (BNT162b2 and mRNA-1273), we assessed humoral and cellular responses vs healthy controls, the incidence of breakthrough infections and adverse events (AEs). Antibodies against spike- and nucleocapsid-protein (anti-S and anti-N) and Spike-specific T-cells responses were quantified at baseline, 21 days after the first and second doses and during follow-up. Results: 182 cirrhotics (85% SARS-CoV-2-naïve) and 38 controls were enrolled. After 2 doses of vaccine, anti-S titres were significantly lower in cirrhotics vs controls [1, 751 (0.4–25, 000) U/mL vs 4, 523 (259–25, 000) U/mL, p=0.012] and in SARS-CoV-2-naïve vs previously infected cirrhotics [999 (0.4–17, 329) U/mL vs 7, 500 (12.5–25, 000) U/mL, (p<0.001)]. T-cell responses in cirrhotics were similar to controls, although with different kinetics. In SARS-CoV-2-naïve cirrhotics, HCC, Child-Pugh B/C and BNT162b2 were independent predictors of low response. Neither unexpected nor severe AEs emerged. During follow-up, 2% turned SARS-CoV-2 positive, all asymptomatic. Conclusion: Humoral response to COVID-19 vaccines appeared suboptimal in patients with cirrhosis, particularly in SARS-CoV-2-naïve decompensated cirrhotics, although cellular response appeared preserved, and low breakthrough infections rate was registered.